Analisis Penerapan Prinsip-Prinsip Syariah Pada Perusahaan Penerbit Surat Berharga Syariah Negara (SBSN) - muhaimin muhaimin (ITB AAS INDONESIA Surakarta, 2022)
This research is motivated by the role of the State Sharia Securities Issuing Company (SBSN) currently in issuing Sharia bonds and acting as an investment guarantee institution and maintaining the company's sharia principles. The purpose of this study is to look at the application of sharia principles by the State Sharia Securities Issuing Company. The research uses a normative approach by collecting primary data sources from laws, government regulations, fatwas and collecting secondary data obtained from books, magazines, articles, journals and other research repositories. These findings show that the relationship between the issuing company and the government is still limited to the company's authority and responsibility in issuing sharia securities. As investment underwriting institutions, these companies act on behalf of investor interests both in front of the court and outside the court. Although the establishment of issuers is only an adoption of the international capital market rather than the concept of Islamic economics, it has applied sharia principles in practices such as avoiding the elements of riba, maysir, gharar, ikhtikar and bai'najasy, risywah, legal certainty, responsibility, and benefits. Meanwhile, the application of principles that may not be in accordance with sharia principles, namely first: there is a default by the government / issuer to investors because the government / issuer is bankrupt so that the return on investment funds at maturity is not met, as promised at the beginning of the Second: there are losses and failures of SBSN issuing companies in carrying out their duties and obligations. Keywords : Application of Sharia Principles.